The acoustic comfort in high-rise hostels: objective and subjective measurements in Malaysia - Dahlan, Nur Dalilah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
Objective and subjective measurement in examining acoustic exposure in high-rise buildings were conducted in three high-rise hostels located in Klang Valley, Malaysia, namely 12th Residential College, University of Malaya (H1), 11th Residential College, Universiti Putra Malaysia (H2), and Murni Student Apartment, Universiti Tenaga Nasional (H3). This study is aimed at assessing the effects of acoustic comfort in high-rise hostel rooms at different floor levels. Measurements were taken in the month of May until July in 2007. One measured room has been selected on the first, fifth and top floors at each block in these high-rise hostels. 298 female students accommodating these hostels participated in the questionnaire investigation. Findings revealed that sound pressure levels increase with the room floor level due to wind and air temperature influences. It is also observed that mean difference for occupants that can hear road traffic noise significantly differed that is similar to the objective measurement where the highest sound pressure level (SPL) detected was in H3, followed by H2 and lastly H1.